POWER AND LOVE IN KHALED HOSSEINI’S AND THE MOUNTAINS ECHOED - DIAH HAYUSULISTYO W (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
POWER AND LOVE IN KHALED HOSSEINI’S AND THE MOUNTAINS ECHOED Diah Hayusulistyo Wardani English Literature Study Program, Faculty of Languages and Arts, Surabaya State University diahwardani2@gmail.com Prof. Dr. FD Kurnia, M.pd. English Literature Study Program, Faculty of Languages and Arts, Surabaya State University Abstrak Naskah ini berkenaan dengan cinta dan kekuatan yang digambarkan secara berbeda pada tiap jenis cinta yang terjadi antara karakter-karakter pada And The Mountains Echoed, Baba Ayub, Qais, Abdullah, Pari Wahdati, Markos Varvaris, Nabi, Pari Abdullah, dan Nila Wahdati. Cinta dan kekuatan telah menjadi topic utama novel ini sejak di terbitkan pada tahum 2013. Karenanya pembelajaran ini focus pada dua masalah utama, (1) Apa jenis-jenis cinta yang digambarkan pada Khaled Hosseini novel And The Mountains Echoed, dan (2) Bagaimana cinta dan kekuatan digambarkan pada Khaled Hosseini novel And The Mountains Echoed. Data- data pada skripsi ini diambil dari novel yang menjadi sumber data utama dan membaca intensif untuk langkah analisa selanjutnya. Terdapat tiga konsep utama yang akan digunakan, pertama adalah teori umum tentang cinta oleh Thomas Lewis, Fari Amini, dan Richard Lanon, kedua yakni jenis-jenis cinta oleh C.S Lewis, dan yang ketigaadalah konsep cinta dan kekuatan oleh Adam Khane. Untuk menjawab masalah yang pertama, pembelajaran ini menggunakan konsep jenis-jenis cinta yang digambarkan oleh karakter-karakter pada novel. Kemudian masalah kedua dijawab dengan konsep dari cinta dan kekuatan oleh Khane dan mencaritau perbedaan penggambaran cinta dan kekuatan pada tiap jenis-jenis cinta. Selain itu, skripsi ini menggunakan kajian pustaka, analisis dan deskripsi. Kajian pustakadigunakan untuk mengumpulkan data yang diperlukan. Analisa digunakan untuk menganalisa data yang telah didapat berdasarkan teori teori. Deskripsi digunakan untuk mendeskripsikan hasil analisa. Setelah melalui analisa panjang dengan menggunakan tiga macam metode diatas, hal ini dapat mengungkapkan penggambaran dari jenis-jenis cinta bahwa Kasih Sayang digambarkan anatara Baba Ayub dan Qais, Abdullah and Pari Wahdati, dan atara Shuja(seekor anjing) dan Pari; Pertemanan digambarkan antara Markos dan Nabi, dan atara Pari Wahdati dan Pari Abdulah; Percintaan digambarkan antara Nabi dan Nila Wahdati; Derma digambarkan oleh Markos Varvaris. Cinta dan kekuatan digambarkan pada tiap jenis-jenis cinta dengan caranya masing-masing.menyatukan atau dengan sengaja menjauhkan dua orang, menuturkan sejarah kehidupan, saling melengkapi dan berjalan beriringan sty sama lain. Katakunci: Cinta, jenis-jenis cinta, cinta dan kekutan Abstract This paper deals with power and love that depicted in different way by each kinds of love that happened between characters of And The Mountains Echoed, Baba Ayub, Qais, Abdullah, Pari Wahdati, MarkosVarvaris, Nabi, Pari Abdullah, and NilaWahdati. Love and power has become the main topic of this novel since it was published in 2013. Thus this study focuses on two major problems, (1) What kinds of love are depicted in KhaledHosseini’s AndThe Mountains Echoed, and (2) How are power and love depicted in KhaledHosseini’sAnd The Mountains Echoed. The data of the thesis is taken from the novel as the main source and intensive reading to next step of analysis. There are three main concepts that will be used, first is the general theory of love by Thomas Lewis, FariAmini, and Richard Lannon, second is kinds of love by C.S Lewis, and the third is the concept of power and love by Adam Khane. To answer the first problems, this study are using the concept of kinds of love that depicted by the characters in the novel. Then the second problems are answered by the concept of power and love by Khane and find out the different depiction of power and love in each kinds of love. Moreover, this thesis used library research, analysis and description. Library research is used to college data needed. An analysis is used to analyze the collected data based on the theories. Description is used to describe the result of analysis. After getting through long analysis by using three kinds of method above, it can reveal the depiction of kinds of love that Affection depicted between Baba Ayub and Qais, Abdullah and Pari, and between Pari and Shuja (a dog); Friendship depicted between Markos and Nabi, and between PariWahdati and Pari Abdullah; Eros depicted between Nabi and NilaWahdati; and Charity, depicted by MarkosVarvaris. Power and love depict by each kinds of love in their own way, unites or intentionally spares the two people, resembles the history of life, complete and walks together side by side. Keywords: Love ;Kinds of Love; Power and love. INTRODUCTION Love is an interesting topic to be discussed. In fact, when we do search in Google about love, we can find that there are 5,930,000,000 posting discuss love. Thomas Lewis, Fari Amini, and Richard Lannon in their book titled A General Theory of Love explain that love can deliver us to understand our self, and it can also shape our personality. From the beginning till the end of human life, love is not merely centered to the activity we have but also to the life power of the mind, decide our feelings, balancing the bodily rhythms, and reconstruct our brain arrangement. Our identities is fixed and determined by relationship that guaranteed by the body’s physiology (2000, p. viii). We can find love in much kind of literary works. Love has always been a favorite topic for poets, novelist and songwriters. It has always relationship with literature. And it is difficult to imagine literature without love. Love becomes so universal theme because of the remarkable variety of its world. Nothing else unite human being so emphatically declares at the same time the plurality of living (Bayley; 3, 1960) One of the novelists that keen on writing love as a topic is Khaled Hosseini, an Afghan-born American physician. He is one of the most widely read and beloved novelist in the world. He has told his reader many things about love with Afghan as a background. The Kite Runner published in 2003 by Riverhed Books, Penguin Group division. Although the themes of the novel are about familial relationship, particularly father and son, the price of disloyalty, the inhumanity of rigid class system, and the horrific realities of war, the main theme of Khaled’d writing was LOVE, described trough that universals aspect. In 2007, The Kite Runner was followed by his second novel A Thousand Splendid Suns, which has spent 21 weeks on The New York Times Best Seller list for paperback fiction and 49 weeks on The New York Times Best Seller, list for hardcover fiction (number one for 15 of those weeks). This novel told the reader about two women find comfort and positive side following their self revelation under the endorsement of particular tradition that used to be perceived as the symbol of female subordination of love. The recent Khaled’s novel is And The Mountain Echoed published in 2013 by River Head Books, a member of Penguin Group in New York. Khaled provide the great example of power and love which makes the readers find refreshment. The main story was bout the great affection between motherless siblings. Other kinds of love also provide by Khaled trough the supporting characters and they are also interesting to be discussed. He explores many ways in which family members love, wound, betray, honor, and sacrifice for another; and how often the readers surprised by the actions of those closest to us, at the time that matter most (And The Mountains Echoed cover). REVIEW OF RELATED LITERATURE General Theory of Love In A General Theory of Love by Thomas Lewis, Richard Lannon, and Fari Amini in their book preface explain that love can deliver us to understand our self, and it can also shape our personality. From the beginning till the end of human life, love is not merely centered to the activity we have but also to the life power of the mind, decide our feelings, balancing the bodily rhythms, and reconstruct our brain arrangement. Our identities is fixed and determined by relationship that guaranteed by the body’s physiology (2000, p. viii). Given the open-loop physiology of mammals and their dependence on limbic regulation, attachment interruptions are dangerous. They ought to be highly aversive. And so they are: like a shattered knee or a scratched cornea, relationship ruptures deliver agony. Most people say that no pain is greater than losing someone they love (2000, p. 93). A child enveloped in a particular style of relatedness learns its special intricacies and particular rhythms, as he distills a string of instances into the simpler tenets they exemplify. As he does so, he arrives at an intuitive knowledge of love that forever evades consciousness. He owes the ignorance of his own heart not to repression but to the brains dual memory design. The frustrating illegibility of love's book is, as software makers say of problems with their programs, a feature and not a bug (2000, p. 116). If a child has the right parents, he learns the right principles—that love means protection, caretaking, loyalty, sacrifice. He comes to know it not because he is told, but because his brain automatically narrows crowded confusion into a few regular prototypes (2000, p. 116). Kinds of Love The author of best seller fantasy novel titled Narnia, C.S Lewis, in his book The Four Loves (1960), argued that love is divided into four types. They are affection,friendship, eros and charity. 1. Affection Storge or affection is a love happened between parents with their offspring and also the offspring for parents. In order to explain this term, Lewis provide an example begun from a mother nursing a baby, a bitch or a cat with a basketful of puppies or kittens; all in squeaking, nuzzling heap together; punings, lickings, baby-talk, milk, warmth, the smell of young life(1960, pp. 53-54) Affection, for Lewis, is enlarging far away beyond the relation between mother and her offspring, it happened in animal life, moreover to our own. The feeling get it satisfaction when get together, more than have everything, warm and so comfortable. This is the kind of love that least discriminating, even the unlucky woman or man that have nothing to offer, but the object of this affection is whoever they are; the ugly, the stupid, even the exasperating. It does not need to find out the source of bounding. The brotherhood relation help someone feel better. It happens also between two people that have different thought for instance a clever young man from the university and an old nurse. Lewis has found that affection happened not only between men and dog but amazingly between dog and cat, Gilbert White claimed has found between horse and hen. It is able to proof that even the barrier of species does not able to influence the affection (1960, pp. 54-55). Lewis claimed that affection has its own standard. Its objects must be familiar. The very day and hour when we fell in love or began a new friendship sometimes became the things to point out. But Lewis doubt that we can guess when is the beginning of the affection. When we recognize to guess when affection started is the time when affection has already been going for some time (1960, p. 55). It is the humblest love, it gives but not expect the replies (1960, p. 56). 2. Friendship Philia or friendship is a love among friends-it is a friendship. Borrowing from Aristotle, Lewis explained that friendship is something that quite marginal not a main course in life's banquet; a diversion; something that fills up the chinks at one's time (1960, p. 88). Lewis argued that people can life and breed without friendship, but not without eros and affection, eros present offspring of our own genes, affection completing our life with comfortableness. Biologically, we do not need friendship (1960, p. 88). Lewis also stated that Companionship is the matrix of Friendship. It is often called as Friendship because many people, when they speak of their “friends” mean only their companions. Friendship arises out of mere Companionship when two or more of the companions find that they have in common insight or interest, for instance a common religion, studies, profession and many more. People share their vision then Friendship is born. They stand together in an excellent solitude (1960, p. 96) Lewis argued, friendship is extremely useful, perhaps necessary for survival, to the individual. A Friend will, to be sure, prove himself to be also an ally when alliance becomes necessary; will lend or give when we are in need, nurse us in sickness, stand up for us among our enemies, do what he can for our widows and orphans. But such good offices are not the stuff of Friendship (1960, pp. 101-102). 3. Eros Eros (ἔρως) for Lewis is love in the sense of 'being in love' or 'loving' someone, as the love that belong to lovers. With the consideration that human have similar sexual function with animal, Lewis described Affection as the love in which our experience seems to come closest to that of the animals, but the discussion of eros is not just simple human sexuality. The complex states for being in love happen when we make sexuality as the part of our subject. That sexual experience can occur without Eros, without being "in love," and that Eros includes other things besides sexual activity, Lewis take for granted. If you prefer to put it that way, Lewis was inquiring not into the sexuality which is common to us and the beasts or even common to all men but into one uniquely human variation of it which develops within "love" what I call Eros. The carnal or animally sexual element within Eros, Lewis intend following an old usage (1960, p. 131) Eros turns the need-pleasure of Venus, a perfectly obvious sense of sexual by those who experience it, could be proved to be sexual by the simplest observations (Lewis, 1960, p. 132), into the most appreciative of all pleasures; but nevertheless Lewis warned against the modern tendency for Eros to become a god to people who fully submit themselves to it, a justification for selfishness, even a phallic religion (1960, p. 133). 4. Charity Lewis recognizes Charity or agape (ἀγάπη) as the greatest of loves, and he sees it as a specifically Christian virtue. He said that this love is really and truly like love Himself. By that, there is a real nearness to God (by Resemblance); but not, therefore and necessarily, a nearness of Approach. (1960, p. 153) According to Lewis, charity is the natural loves that are not self-sufficient. Charity revealed as goodness, and finally as the whole Christian life in one particular relation, must come to the help of the mere feeling if the feeling is to be kept sweet. It is the love of God. To explain this, he likened to the example of garden that needs tending. They cannot be their beautiful selves without allegiance to God (1960, p. 163). Power and Love Khane in his book titled Power and Love: A Theory and Practice of Social Change, state that power is the way we change one condition, or in the similar term with make a new social realities. The generative aspects of power itself are the entire will pointed to ‘get ones job done’. Power expresses our purposefulness, wholeness, and agency. Although power is the drive to realize one’s self, the effect of power goes beyond one’s self (2010, p. 13). Love according to Khane is what makes power generative instead of degenerative (2010, p. 7). Love is not something that suddenly strikes us—it is an act of the will. By “an act of will,” Love is an intentional disposition toward another person (Khane, 2010, p. 31). Khane also quote some expert statement about love: Humberto Maturana, a Chilean cognitive biologist who also worked with Peter Senge at the Society for Organizational Learning, offers a similar definition: “Love is the domain of those relational behaviors through which another (a person, being, or thing) arises as a legitimate other in coexistence with oneself”. And Khane also borrows the idea of Jungian Robert Johnson, who wrote “Love is the one power that awakens the ego to the existence of something outside itself.” All of these definitions, from the worlds of management, biology, and psychology, are congruent with Paul Tillich’s from theology. Love is the other-acknowledging, other-respecting, other helping drive that reunites the separated (2010, p. 32). Khane also pictures how love and power condition while both of them unbalance by saying “We fall down painfully when, like a scarecrow or a marionette, our two legs become disconnected from each other. We fall down when our power and our love become polarized: when our power is without love and our love is without power. We fall down when, intentionally or unintentionally, we make the elementary and common error of treating the relationship between power and love, which is a dilemma, as if it was a choice (2010, p. 57). Khane has done observation about it with himself; there are three states from progression: when we are falling, we are unable to co-create new social realities; when we are stumbling, we are unstably able; and when we are walking, we are confidently able. This does not mean that we can always progress linearly from one state to the next; often, lacking awareness or capacity, we regress. In fact Khane has sometimes progressed and sometimes regressed, which is why Khane related the stories in his book in a non-chronological order (2010, p. 56). According to Khane working through in our individual actions (bold undertaking) the same progression from falling to stumbling to walking that I have described at the level of collective actions. First, we must pay attention to and keep in connection our power and our love. Second, we must balance ourselves by building up and bringing in our weaker drive. And third, we must practice moving forward through shifting fluidly between these two drives, so that they become one (2010, p. 128). ANALYSIS The Depiction of Kinds of Love The Depiction of Storge-Affection - Baba Ayub and Qais Storge love firstly depicted from the character of Baba Ayub in the tale that told by Saboor to their children. In Saboor’s story Baba Ayub is father who deeply loves his children, but he has one deeper to one of them, Qais. Though he loved all of his children, Baba Ayub privately had a unique fondnees for one among them, his youngest, Qais, who was three years old. (ch.1, p.2) From the quotation above we know that Qais is Baba Ayub’s son, the kind of love shared between Baba Ayub and Qais or vice versa is the Storge love or affection. Lewis argued that the feeling get its satisfaction when get together, more than everything, warm and so comfortable (1996, p. 55). Of course that affection also happened between Qais and his father Baba Ayub as Khalid told in his novel: When Baba Ayub came home after a long day’s work, Qais would run from the house face-first into his father’s belly, […]. Baba Ayub would lift him up and take him into the house, and Qais would watch with great attention as his father wash up, and he would sit beside Baba Ayub at suppertime. After they had eaten, Baba Ayub would sip his tea, watching his family, picturing a day when all of his children married and gave him children of their own, when he would be proud patriarch to an even greater brood. (ch.1, p. 3) The quotation above explain how happy was Qais feeling when he knew that this father is home from work, it proves that Qais affection to his father get it’s comfortableness when he was gathered with his father. And so did Baba Ayub, with his affection feeling Baba Ayub lift Qais up and take him into the house, when Baba Ayub take a look at all his children he was imagine that this togetherness of affection felling will be more great and prideful when he get grandchildren from them. - Abdullah and Pari Secondly storge or affection depicted by love of Abdullah to Pari, storge love here is not the usual storge love like has been discussed before that generally it happen between parents to their offspring or vice versa, in case, the storge love here belongs to the relation between siblings. Abdulah was Pari’s brother, because their mother has been passed away. Abdullah substituted the mother role in taking care Pari while she was a baby. Abdullah love to Pari here is a storge love, not a brotherhood love, but more, it is affection as parents to the child. He was the one raising her. It was true. Even though he was still a child himself. Ten years old. When Pari was an infant, it was he she had awakened at night with he squeaks and mutters, he who walked and bounce her in the dark. He had changed her spoiled diapers. He had been the one to give Pari her baths. […]. Thus the care had fallen to Abdullah, but he didn’t mind at all. He did it gladly. He loved the fact that he was the one to help with his firs step, to gasp at her first uttered word. This was his purpose, he believed, the reason God had made him, so he would be there to take care of Pari when He took away their mother. (ch. 2, p. 31) As C.S. Lewis explanation about Storge, he provides an example begun from a mother nursing baby, a bitch or cat with a basketful of puppies or kittens; all in squeaking, nuzzling heap together; punings, lickings, baby-talk, milk, warmth, the smell of young life (1960, p. 54). This condition happen also with Abdullah and pari even thogh Abdullah is not her mother, from the quotation above we know that Abdullah was the one who nursing her while he was a baby, he awakened at night with, he walked and bounce her in the dark. He changed her spoiled diapers. He had been the one to give Pari her baths. - Pari and Shuja (a dog) Shuja was a dog but, it never be impossible for Lewis storge/affection happened between them. He avoided everone in Shadbagh but Pari. It was for Pari that Shuja lost all composure. His love for her was vast and unclouded. She was his univers. In the mornings, when he saw Pari stepping out of the house, Shuja sprang up, and his entire body shivered. The stump of his mutilated tail waged wildly, and he tap dance like he was treading on hot coal. He prance happy circle around her. All day the dog shadowed Pari, sniffing at her heels, and at night, when they parted ways, he lay outside the door, forlorn, waiting for morning. (ch. 2, p. 25) Love between Shuja and Pari is affection, from the quotation above we know that Shuja used to stay near Pari, as what C. S. Lewis explained that affection get it satisfaction when get together, more than everything (1960, p. 54-55). This may help to answer of why Shuja was happy to cirle around Pari, shadowed Pari all the day, sniffing at Pari’s heels, and lay outside the door in the night to waiting for morning, to saw Pari stepping out of the house again, and sprang up, and tap dance like a treading on hot coal. The Depiction of Philia-Friendship - Markos and Nabi In Khaled’s, character of Markos and Nabi have shared philia/ friendship. Their companionship has been build up after they were spending much time together. They had been known each other for about seven years. In his latter Nabi wrote: Let me state now what a pleasure it has been to know you over the last seven years, Mr. Markos. As I write this, I think foundly of our yearly ritual of planting tomatoes in the garden, your morning visit to my small quarters for tea and pleasanty, our impromptu trading of Farsi and English lessons. I thank you for your friendship, your thoughtfulness, and for the work that you have undertaken in this country, and I trust that you will extend my gratitude to your kindhearted colleagues as well, especially to my friend Ms. Amra Ademovic, who has such capacity for compassion, and to her brave and lovely daughter, Roshi. (ch. 4, p. 73) Companionship is the matrix of Friendship (1960, p. 96). Companionship between Nabi and Markos happened in a long time, it was seven years. They have in common insight or interest: planting tomatoes in the garden, morning visit to Nabi’s small quarters for tea and pleasanty, and also their impromptu trading of Farsi and English lessons. To Lewis, Friendship exhibits a glorious "nearness by resemblance" to Heaven itself where the very multitude of the blessed (which no man can number) increases the fruition which each has of God. For every soul, seeing Him in her own way, doubtless communicates that unique vision to all the rest (1960, p. 93-94). As what had Nabi written in his latter that he trusted Mr. Markos will extend Nabi’s gratitude to his kindhearted colleagues as well, […] (c. 4, p. 73). Frinedsihip by C.S Lewis is depicted between Nabi and Markos, when Lewis argued that the least jealous of loves is the true friendship. Two friends delight to be joined by a third, and three by a fourth, if only the newcomer is qualified to become a real friend. For in this love "to divide is not to take away." this is depicted on the quotation above, beside friendship happened between Nabi and Markos, They have other friend, Ms. Amra Ademovic. Then, it is known that friendship depicted trough Nabi and Markos. - Pari Wahdati and Pari Abdullah Pari Wahdati was Abdullah’s sister and Pari Abdullah was Abdullah’s daughter. Even though, their generation is different, but they were depict a good friendship as well. But how could this two personality that just meet each other when one was a fifties old woman and one other was the twenties girl? , Moreover it seems contradictive with Lewis theory about friendship that arise out of mere companionship. This quotation from Khaled’s provides the answer: And so Baba’s little sister, Pari, was my secret companion, invisible to everyone but me. […]. I saw her in the bathroom mirror when we brush our teeth side by side in the morning, we dressed together,. She followed me to school and sat close to me in class—looking straight ahead at the board, I could always spot the black of her hair and the white of her profile out of the corner of my eye. I took her with me to the playground at recess, feeling her presence behind me when whooshed down a slide, […]. (ch. 9, p. 347) The quotation above answered that actually Pari Wahdati and Pari Abdullah was truly depicted Lewis’s Philia love or friendship. They were companion as Lewis’s has argued. Pari Wahdati in the shape of little girl was life in Pari Abdullah’s daily. They have done many things together, wherever, whenever. The Little image of Pari Wahdati never escapes from Pari Abdullah’s eyes. To emphashise more about this this two Pari’s Friendship, another quotation provide the support: Sometimes, when no one was around we ate grapes and talked and talked --about toys, which cereal was tastiest, cartoons we like, school kids we didn’t, which teacher’s we mean. We shared the same favorite color (yellow), favorite ice cream (dark cherry), TV show (Alf), and we both want to be artist when we grew up. (ch. 9, p. 347) Lewis argued that Friendship arises out of mere Companionship when two or more of the companions find that they have in common insight or interest (1960, p. 96). This is what has been depicted by Pari Wahdati and Pari Abdullah, they have in common insight or interest as what the quotation told, they talked about toys, the tastiest cereal, cartoons they like, school kids they didn’t, which teacher’s they mean. According to Lewis, people share their vision then Friendship is born. They stand together in an excellent solitude (1960, p. 96). Pari Wahdati and Pari Abdullah shared the same favorite color (yellow), favorite ice cream (dark cherry), TV show (Alf), and both of them want to be artist when we grew up. That is why even though Pari Wahdati in the shape of a little girl was just only Pari Abdullah’s imagination, they were as a friend stand together in excellent solitude. The Depiction of Eros-Romance - Nabi and Nila Wahdati Nabi was the assistance of Nila Wahdati’s husband. From the first time he meet Nila when he drove Mr. Wahdati fisited Nila’s house before they were married, Nabi felt that Nila was “a particular woman” like what Lewis stated, it shown clearly while Nabi describe about Nila in his first sight. It was then that the front gates opened and a black-haired young woman emerge. She wore sunglases and a short-sleeved tangerine-colored dress that fell short of the knees. Her legs were bare, and so were her feet. I did not know wheather she had noticed me in the car, and, if she had, she offred o indication. She rested the heel of one foot against the wall behind her and, when she did, the hem of her dress pulled up slightly and thus revealed a bit of the thigh beneath. I felt a burning spread down from my cheeks to my neck. (ch. 4, p. 80) According to Lewis in Eros, a need, at its most intense, sees the object most intensively as thing admirable in her (1960, p. 136). From the quotation above Nabi express his admiration to Nila by describing the beautiful of Nila in vivid way. Begin from that moment Nabi has made up his opinion that Nila is special for him. Moreover, in Lewis argument founded that the admiration of Nabi to Nila continued after she moved to Mr. Wahdati’s house: I had never in my life encountered a young woman like Nila. Everything she did—the way she spoke, the way she walked, dressed, smiled—was a novelty to me. Nila pushed against every single notion I had ever had of how a woman should behave, […]. (ch. 4, p. 87). Lewis argued that the complex states for being in love happened when we make sexuality as the part of subject (1960, p. 21). That what also present between Nabi and Nila, sometimes the admiration bring sexuality as the part of subject. The Depiction of Charity-Agape - Markos Varvaris and Christ The depiction of Lewis’s Charity in Khaled Hosseini’s AND THE MOUNTAINS ECHOED found trough one supporting character named Markos Varvaris that known as a Christian from the quotation below. This evening I come home from clinic and find a massage from Thalia on the landline phone in my bedroom. I play it as I slip of my shoes and sit at my desk. She tells me she has a cold, one she is sure she picked up from Mama, then she ask after me, ask how work is going in Kabul. At the end, just before she hangs up, she says, Odie goes on and on about how you don’t call. Of course she won’t tell you. So I will. Markos. For the love of Christ. Call your mother. You ass (ch. 8, p. 279). The quotation above is the part of novel that told using the point of view of Markos Varvaris, from the quotation especially from Thalia’s said ‘For the love of Christ. Call your mother’, we got that Markos was a Christian. As Lewis argued that, Charity is the love for the Christian virtue (1960, p. 153). Markos Varvaris was the character that depicts Lewis’s Charity. Markos Varvaris was the doctor of plastic surgeon. He ungrudgingly leaves his city and his beloved mother to go to Kabul to help people there. This is depicted Lewis explanation of charity trough the imagery of garden that he said when God planted a garden He set a man over it and set the man under Himself. When He planted the garden of our nature and caused the flowering, fruiting loves to grow there, He set our will to "dress" them (1960, p. 164). What Markos did is to “dress” his life, by his decision to help people. Lewis said that it is easy to love fellow-creatures less and to imagine this is happening because we are learning to love God (1960, p. 165). To help people like what Markos did is one of the reflections of loving the fellow-creatures, because he was learning to love his God. The Depiction of Power and Love The depiction of Power and Love - Baba Ayub and Qais Baba Ayub and Qais depicted storge love, a great affection of parent and offspring. From the story, Baba Ayub beloved son’s Qais has to be given to the div, off course this makes Baba Ayub felt down. Tomas Lewis et al argued that love decides our feeling (2000, p. viii). No pain is greater than losing someone they love (2000, p. 93). Baba Ayub feeling of great pain depicted from the quotation below: Where was I? Ah yes. There followed a forty-day mourning period. Every day, neighbors cooked meals for the family and keep vigil them. People brought over what offerings they could—tea, candy, bread, almonds—and they brought as well they condolences and sympathies. Baba Ayub could hardly bring himself to say so much thanks. He sat in the corner, weeping, streams of tears pouring from both eyes as though he meant to end the village’s streak of droughts with them. You wouldn’t wish his torment and suffering on the vilest of men (ch. 1, p. 6) From the quotation above, we got that love has decide Baba Ayub feeling from the tough man of family head into torment and suffering on the vilest of men, sorrowful, until tears pouring from both the eye of a “man”, and it is off course depict Lewis et al theory that no pain is greater than losing someone they love (2000, p. 93). That theory also emphasized with another argument that the daily anodynes: our lovers, spouses, children, parents, and friends delivering the magic of forgetfulness from the twinging ache of mammalian loneliness (2000, p. 96). Khane borrow the idea of Jungian Robert Johnson, who wrote “Love is the one power that awakens the ego to the existence of something outside itself” (2010, p. 32) when ego, according to Freud is the one that can produce—or feel anxiety (2009, p. 33). From that theory that power came as the same thing happened with Baba Ayub, after a long time he passed to receive the loss feeling of his beloved son, Baba Ayub woke up. The depiction of Power and Love – Abdullah and Pari Wahdati Abdullah and Pari Wahdati depicted a deep Affection love. At the moment when they were child they were being separated, their father sold little Pari to Wahdati family. Then, the ten years Abdullah feeling a deep lost. According to Lewis et al A child enveloped in a particular style of relatedness learns its special intricacies and particular rhythms, as he distills a string of instances into the simpler tenets they exemplify (2000, p. 116). Both of them feeling lost of each other. Many years has passed till they grow as an old person in the separated places, Pari at that time was too small to remember everything, but their Power and Love resembles trough generation till unite them again even in a very late of time. Khaled argued that Love has two sides, one generative and the other degenerative. Our love is generative when it empowers us and others: when it helps us, individually and collectively, to complete ourselves and grow. Our love is degenerative sentimental and anemic, or worse—when it overlooks or denies or suffocates power (2010, p. 50). This theory depicted by Pari, Pari’s love is a generative because it empowers her and Abdullah, help them individually and collectively, complete them self, as the quotation below explained. We are passing by Redwood City on our way south. I reach across her lap and point out the pessanger window. “Do you see that building? The tall one with the blue sign?” “Yes?” “I was born there.” “Ah, born?” she turns her neck to keep looking as I drive us past. “you are lucky.” “How so?” “To know where you came from.” “ I guess I never gave it much thought” “Bah, of course not. But it is important to know this, to know your roots. To know where you started as a person. If not, your own life seems unreal to you. Like a puzzle. Vous comprenez? Like you have missed the beginning of a story and now you are in the middle of it, trying to understand.” I imagine this is how Baba feels these days. His life, riddled with gasp. Every day mystifying story, a puzzle to struggle through. (ch. 9, p. 356) From this quotation we got that Pari depicted Khane argument that her love is generative when it empowers us and others: when it helps us, individually and collectively, to complete ourselves and grow. Her Love and Power bring her into and understanding that it is important to know your roots. To know where you started as a person. If not, your own life seems unreal to you. Like a puzzle. Vous comprenez? Like you have missed the beginning of a story and now you are in the middle of it, trying to understand. The same thing has happened with Abdullah, which his daughter explained that what Abdullah feels these days was his life, riddled with gasp. Every day was mystifying story, a puzzle to struggle through. When both of them meet each other, suddenly Abdullah was on the condition of senility. As Lewis et al explained Given the open-loop physiology of mammals and their dependence on limbic regulation, attachment interruptions are dangerous. They ought to be highly aversive. And so they are: like a shattered knee or a scratched cornea, relationship ruptures deliver agony. Most people say that no pain is greater than losing someone they love (2000, p. 93). A deep lost that Abdullah felt when he has to separate with Pari while they were child has made an agony which hurt Abdullah psychology in her old. His memory was stuck that the one he lost is her little sister Pari that is a little girl. He could not accept the reality that she was growing into an old woman right now. But Pari was not give up she tries hard to wake his brother about this thing trough another way. The depiction of Power and Love – Pari and Shuja (a dog) It has been known from the analysis of C. S Lewis’s Kinds of Love depiction that storge/affection love happened between Pari and Shuja. Eventhough it is known that Pari was a human being and Shuja was a dog but, it has been proved by the C.S Lewis theory and also Gilbert White. As like other loves, animal’s love also has a power. The depiction of Khane theory of Powe and Love also find in it. His days in Shadbagh were numbered, like Shuja’s. He knew this now. There was nothing left for him here. He had no home here. He would wait until winter passed and the spring thaw set in, and he would rise one morning before dawn and he would step out the door. He would choose a direction and he would begin to walk. He would walk as far from Shadbagh as his feet would take him. And if one day, trekking across some vast open field, despair should take hold of him, he would stop in his tracks and shut his eyes and he would think of the falcon feather Pari had found in the desert. He would picture the feather coming loose from the bird, up in the clouds, half a mile above the world, twirling and spinning in violet currents, hurled by gusts of blustering wind across miles and miles of desert and mountains, to finally land, of all places and against all odds, at the foot of that one boulder for his sister to find. It would strike him with wonder, then, and hope too that such things happened. And though he would better, he would take heart, and he would open his eyes, and walk. (ch. 2, p. 49) Khane argued that Love and Power condition while both of them unbalance we will fall down painfully when, like a scarecrow or a marionette, our two legs become disconnected from each other. We fall down when our power and our love become polarized: when our power is without love and our love is without power. We fall down when, intentionally or unintentionally, we make the elementary and common error of treating the relationship between power and love, which is a dilemma, as if it was a choice (2010, p. 57). This is depicted by Shuja, he has fell down, unintentionally, he made the elementary and common error of treating the relationship between power and love after he lost Pari, that is why he was walking far away tried to find her again somewhere. He was on the dilemma and he has chosen to over it by keep walking to find Pari. The depiction of Power and Love – Nabi and Markos Nabi and Markos have shared philia/ friendship, their companionship has been build up after they were spending much time together for abot seven years. When Khane argued that Power is the way we change one condition, or in the similar term with make a new social realities (2010, p. 13), Nabi and Markos love of friendship has depicted it. They made a new social reality, if two different thing is not easy to bound, they proof this is not always happened. Markos was a Christian and Nabi was a Muslim, Markos was a plastic surgeon doctor which is educated person, but Nabi was an uneducated servant, but Power of friendship they shared has change one condition that difference can even unite them. Khane argued that Love is something that makes power generative instead of degenerative (2010, p. 7). Love is not something that suddenly strikes us—it is an act of the will. By “an act of will,” Love is an intentional disposition toward another person (Khane, 2010, p. 31). Love between Markos and Nabi is a friendship love. Their friendship love is generative too. It is not strike any of them to have friendship outside theirs. The proof is shown in the quotation below: Let me state now what a pleasure it has been to know you over the last seven years, Mr. Markos. As I write this, I think foundly of our yearly ritual of planting tomatoes in the garden, your morning visit to my small quarters for tea and pleasanty, our impromptu trading of Farsi and English lessons. I thank you for your friendship, your thoughtfulness, and for the work that you have undertaken in this country, and I trust that you will extend my gratitude to your kindhearted colleagues as well, especially to my friend Ms. Amra Ademovic, who has such capacity for compassion, and to her brave and lovely daughter, Roshi. (ch. 4, p. 73) Love as Khane said that is not strike any of them (Khane, 2010, p. 31) was shown obviously here from that quotation we see that beside their friendship, Markos and Amra Ademovic was friend too. It was not closed the possibility that any of them will have other friends outside the boundaries, which is allowed, never strike, because it was love of friendship. Khane said that love is generative (Khane, 2010, p. 31). Love of friendship between Markos and Nabi was also generative because their love is growing well till the end of Nabi’s life, even after Nabi’s death, Markos love trough Nabi still alife by the fact that he keep any message that Nabi left, and make his wish came true. The depiction of Power and Love – Pari Wahdati and Pari Abdullah Power and Love of Khane between Pari Wahdati and Pari Abdullah was always depicted Khane theory of Walking states. They were always walking rhythmically, engage Power and Love, each balancing out and bringing in and building up the other. When they walk, they move forward, learning as they go (2010, p. 103). “I am really sorry,” I say “Why are you sorry?” “That you found each other too late.” “But we have found each other, no?” she says, her voice cracking with emotion. ”And this is who he is now. It’s all right. I feel happy. I have found a part of myself that was lost.” She squeezes my hand. “And I found you, Pari” Her words tug at my childhood longings. I remember how when I felt lonely, I would whisper her name—our name—and hold my breath, waiting for an echo, certain that it would come someday. Hearing her speak my name now, in this living room, it is as though all the years that divided us are rapidly folding over one another again and again, time accordioning itself down to nothing but the width of photograph, a postcard, ferrying the most shining relict of my childhood to sit beside me, to hold my hand and say my name. Our name. I feel a tilting, something clicking into place. Something ripped a long ago being sealed again. And I feel a soft lurch in my chest, the muffled thump of another heart kick-starting anew next to my own. (ch. 9, pp. 391-392) The engagement of their Love and Power were obviously showed when Pari said that “I feel a tilting, something clicking into place. Something ripped a long ago being sealed again. And I feel a soft lurch in my chest, the muffled thump of another heart kick-starting anew next to my own”. So that it find that they Love and Power of a friendship is balance and building up together, because each of them fell the same thing. According to Khane the relation of power and love will give its understanding while we understand the nature of love itself. Khane argued that Love has two sides, one generative and the other degenerative. Our love is generative when it empowers us and others: when it helps us, individually and collectively, to complete ourselves and grow. Our love is degenerative sentimental and anemic, or worse—when it overlooks or denies or suffocates power (2010, p. 50). Power and love relation between Pari Wahdati and Pari Abdullah is on the side of generative, their power and love is empowers each other. Pari Abdullah felt down when she has to face his Father was in the very bad condition till she has to decide sent him to the nursing house. She felt very sad of this but, she was helped by the presence of Pari Wahdati which was always stayed beside her, support her, and makes her dreams comes true. The depiction of Power and Love – Nabi and Nila Wahdati Nabi and Nila Wahdati shared Eros love, but they depicted Khane Power and Love Stumbling states. According to Khane stumble when our power dominates our love, or our love dominates our power. Stumbling is not controlled and smooth; it is uncontrolled and unstable. When we stumble, we move forward, but haltingly and erratically and always at risk of falling down (2010, p. 75). What happened between Nabi and Nila was their loves dominate their power. This was happening because Nabi was the assistance of Nila Wahdati’s husband. From the first time he meet Nila when he drove Mr. Wahdati fisited Nila’s house before they were married, Nabi felt that Nila was “a particular woman” like what Lewis stated, it shown clearly while Nabi describe about Nila in his first sight. But still, they could not unite because Nabi was a loyal servant, he respected his lord a lot which is Nila’s husband. And Nila decide to keep his marriage by avoid Nabi’s love and keep treating Nabi as a servant. As depicted trough the quotation below. To this I could think of nothing to say. I longed to climb into the back seat beside her and pull her into my arms, to soothe her with kisses. Before I knew what I was doing, I had reached behind me and taken her hand into mine. I thought she would withdraw but her fingers squeezed my hand gratefully, and we sat there in the car, not looking for at each other but ant the plains around us,[…]. Nila’s hand in mine, I looked at the hills and the power poles.[…], and I would happily sat there until the dark. “Take me home,” she said at last, relasing my hand. “I am going to turned in early toninght.” “Yes, Bibi Sahib.” I cleared my throath and dropped the shift into first gear with a slightly unsteady hand. (ch. 4, p. 95) Their Eros love was expressed trough kisses and holding hand. But after that all, they are conscious that what they have done was exactly wrong. So they decide to forget everything and back to their real life as a lord and servant. Nila statement of “Take me home,” she said while releasing Nabi’s hand. “I am going to turned in early to night” was obviously indicate that she emphasized herself as Nabi’s lord that her order must be obeyed. And so did Nabi to adrees Nila “Yes, Bibi Sahib” was to show he recognize that he was her servant and respect Nila as his boss. The depiction of Power and Love – Markos Varvaris and Crist As a Christian, Markos Varvaris depicted Charity love, a love of God. His love was reflected from his action that shown his care and love of the fellow-creatures, especially, his sympathy to Manaar. Like what C. S. Lewis mentioned that Lewis found the fact that humans cannot even remain themselves and do what they promise to do without God's help from this it can be said that the loves prove that they are unworthy to take the place of God (1960, p. 170). It is the same thing happened with Markos trough Manaar he got an inspiration of how he could love his God deeper. And Khane Power and Love of Walking states is depicted here. That in the Walking states we engage our power and our love, each balancing out and bringing in and building up the other. When we walk, we move forward, learning as we go (103, 2010). Markos experienced the same thing. I am not saying that Manaar changed everthing. He did’t. I stumble around the world for still another year before I finally find medical school application. In between Manaar and the application are the two weeks I spent in Damascus, of which I have virtually no memory other than the grinning faces of two women with heavily lined eyes and a gold tooth each. Or the three months in Cairo in the basement of ramshackle tenement run by a hashish-addicted landlord. I spent Thalia’s money riding buses in Iceland, tagging along with a punk band in Munich. In 1977, I break an elbow at an antinuclear protest in Bilbao. (ch. 8, p. 317) Lewis statement of the fact that humans cannot even remain themselves and do what they promise to do without God's help, was absolutely true. In the quotation, it is happened in Markos “I am not saying that Manaar changed everthing. He did’t.” the quotation obviously showed how Markos understand that the one who changed him is not Manaar anyway, but God. He emphasized, “He did’t”, to indicate recognize that God did it. The Power and Love of Khane in Walking sates depicted in Markos when he realized to continue sharing and caring his love trough the fellow creature. His decision to take medical school becomes the perfect way. Khane said that when we walk, we move forward, learning as we go. Markos move forward to take a step ahead in his passion to love, care, and help the fellow creature as the way he is learning to love God, Christ. According to Khane, working through in our individual actions (bold undertaking) the same progression from falling to stumbling to walking that he have described at the level of collective actions. First, we must pay attention to and keep in connection our power and our love. Second, we must balance ourselves by building up and bringing in our weaker drive. And third, we must practice moving forward through shifting fluidly between these two drives, so that they become one (2010, p. 128). Markos effort to love his God is not complete enough, he has Love and Power, he has paid attention to and keep in connection our power and our love by being a doctor of plastic surgeon ang help people with their problems. He has balanced his selves by building up and bringing in his weaker drive. He moved to Kabul- Afghan to help the victim of war. And he practiced the two drives, but they have not find it become one. Because his mother is not acquiesced his son was far away from her, but after her mother said that she was sincere, everything changed. CONCLUSION Based on the previous chapter, we can infer that there are two points of this thesis can be seen: First is there are four kinds of love (Affection, Friendship, Eros and Charity) depicted in Khaled Hosseini’s And The Mountains Echoed. Affection is the love that full of comfortableness, depicted between the characters of Baba Ayub and Qais, Abdullah and Pari, and between Pari and Shuja (a dog). Friendship is the love that shaped by companionship and similarities depicted between the characters of Nabi and Markos Varvaris, and between Pari Wahdati and Pari Abdullah. Eros is romance, love between lovers that sometimes involve Venus in more appreciative way depicted between Nabi and Nila Wahdati. And Charity is the natural and greatest love, love of God, in the view of Christian virtue depicted by Markos Varvaris. The second is that power and love depicted in each kinds of love in their own way, unites or intentionally spares the two people, resembles the history of life, complete and walks together side by side. Between Baba Ayub and Qais, power and love has bring Baba Ayub sincerely let Qais live in the div place for Qais happiness and life. Power and love depicted between Pari and Abdullah that make them unite again from fortyish separated in a long distance. Power and love between Shuja and Pari depicted in unbalance condition, this made Shuja made the elementary and common error of treating the relationship between power and love after he lost Pari. Markos and Nabi are depiction in power and love in the states of Walking, balance out and bringing in and building up the other, so they are able to complete each other necessity, until Markos resembled Nabi’s life history. Pari Wahdati and Pari Abdullah is also depiction power and love in Walking states, power and love of a friendship is balance and building up together, because each of them fell the same comfortableness as they are together. Power and love between the lovers Nabi and Nila Wahdati depicted in the states of stumbling, in which their loves dominate their power, they were in the risk of falling down, so they prefer to avoid falling by back to the reality as they were a servant and boss. The last is the depiction of power and love by Markos Varvaris and God. Markos depicted the Walking sates when he realized to continue sharing and caring his love trough the fellow creature and he take an action to create it by applying medical school. Markos move forward to take a step ahead in his passion to love, care, and help the fellow creature as the way he is learning to love God, Christ. All those above, are prove that love and power are able to make step forward in human life, but they can also bring someone falling deeper, it depends on our effort to choose one of them. REFERENCES Bayley, John. 1960. The Character of Love. London: Constable, Inc. Falvlun. 2012. Agape Love vs Philia Love. Available at: http://www.religiousforums.com/forum/general religious-debates/76681-agapelovevs-philia love.html. Feist, Jess, and Feist, Gregory J. 2009. Theory of Personality 7th Edition. USA: The McGraw−Hill Companies. Hosseini, Khaled. 2013. And The Mountains Echoed. New York: Riverhead Books a Member of Penguin Group (USA), Inc. Khane, Adam Morris. 2010. Power and Love. California : Berrett-Koehler Publishers, Inc. Lewis, C.S. 1960. The Four Loves. New York: Harcourt Lewis, Thomas, et al. 2000. A General Theory of Love. USA: Random House, Inc. Purwaningsih, Indah. 2010. Women’s Self Revelation in Response to Afghan Tradition as Represented in Khaled Hosseini’s A Thousand Splendid Suns. Surabaya: UNESA Internet Sources: http://en.wikipedia.org/wiki/Love, retrieved on October 29, 2013 9:49 http://www.us.penguingroup.com/static/rguides/us/kite_runner.html, retrieved onNovember 19, 2013 11:40 http://en.wikipedia.org/wiki/Khaled_Hosseini, retrieved on January 24, 2014 9:45 http://en.wikipedia.org/wiki/The_Four_Loves, retrieved on November 5, 2013 11.05 pm